Uji Aktivitas Antibakteri Ekstrak Daun Bridelia micranth Lombok pada Escherichia coli - Faizul Bayani; Endang Sudiana; Ade Sukma Hamdani; Ida Wahyuni; Jamilul Mujaddid; Hulyadi Hulyadi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The aim of this research is to identify the antibacterial activity of Bridelia micranth Lombok extract on the pathogenic bacteria Escherichia coli. The independent variable in this study was the concentration of Bridelia micrantha leaf extract. The concentration of Bridelia micrantha leaf extract in this study was varied from 20%, 40%, 60%, and 80%. The dependent variable is the ability of Bridelia micrantha leaf extract as an antibacterial. The antibacterial ability of Bridelia micrantha leaf extract was measured based on the diameter of the clear zone with three repetitions. As a comparison, an antibacterial is used, namely amoxicillin. Data analysis in this research was carried out descriptively, and then non-parametric tests were carried out to test the homogeneity of the data. In this study, the antibacterial ability of Bridelia micrantha leaf extract was discovered. At a concentration of 20%, the average diameter of the inhibitory zone was 2.5 mm which was categorized as none (resistance), 40% concentration was 9.83 mm in the non-existent category (resistance), 60% concentration was 13.66 in the weak category (intermediate), and at a concentration of 80% 16.5 mm is in the medium (sensitive) category. The research results indicated that Bridelia micrantha leaf extract had antibacterial activity against Escherichia coli bacteria. When compared with amoxicillin, the ability of Bridelia micrantha leaf extract as an antibacterial is still lower. Amoxicillin was able to inhibit the growth of Escherichia coli by 18.13 mm, while the highest ability of Bridelia micrantha leaf extract was 16.5 mm. Based on Ministry of Health regulations, antibacterials can be used if the inhibition zone is between 14-18 mm. So, Bridelia micrantha leaf extract can be used as an antibacterial, but it needs to be tested further before being applied to the public.